2016
DOI: 10.1039/c6ra17454j
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition and combustion of cocrystals of CL-20 and linear nitramines

Abstract: Cocrystals of CL-20/nitramine decompose into components at the melting point. Subsequent evaporation of nitramine leaves CL-20 in the amorphous state. The lack of the crystal lattice results in an increased decomposition rate of CL-20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…CL-20 (2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane)-based composites could possibly replace various explosive compounds such as RDX and HMX to produce high-performance explosives because of its excellent properties of density and energy. However, it cannot be quickly transmitted after experiencing rapid high-low temperature changes since its poor thermal property, which is easy to form the “hot spot” and seriously endanger the safety and reliability of the weapon system [ 1 7 ]. Therefore, it is of great significance to effectively improve the thermal conductivity and reduce the impact sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…CL-20 (2,4,6,8,10,12-hexanitro-2,4,6,8,10,12-hexaazaisowurtzitane)-based composites could possibly replace various explosive compounds such as RDX and HMX to produce high-performance explosives because of its excellent properties of density and energy. However, it cannot be quickly transmitted after experiencing rapid high-low temperature changes since its poor thermal property, which is easy to form the “hot spot” and seriously endanger the safety and reliability of the weapon system [ 1 7 ]. Therefore, it is of great significance to effectively improve the thermal conductivity and reduce the impact sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of CL-20 and RDX on basic properties of CMDB propellants were investigated, the major findings could be summarized as follows: 1) The calculations on energetic properties for CL-20/RDX-CMDB propellants showed that energetic properties of propellant with CL-20 were superior to of propellant with RDX. 2) The data on burning rate revealed that with the increase of RDX/CL-20 mass fraction in the propellants, the burning rates at low pressure (2-8 MPa) remained almost the same but differ observably at high pressure (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). With the increase of CL-20 mass fraction in the propellants, the burning rates of propellants could be enhanced significantly, but the burning rates of propellants containing RDX decreased.…”
Section: Resultsmentioning
confidence: 97%
“…Hexanitro hexaazaisowurtzitane (HNIW or CL-20) is superior to hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) and cyclo-tetra-methylenetetranitramine (HMX) with respect to density, enthalpy of formation, and oxygen balance [6][7][8][9]. CL-20 has evoked interest as a promising candidate, replacing various energetic compounds such as RDX, HMX and ammonium perchlorate (AP), for realizing the eco-friendly, high-performance, highspecific impulse(Isp), minimum signature propellants for futuristic missiles and space missions [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown previously that the evaporation of volatile compounds, such as 2,4‐dinitro‐2,4‐diazapentane (DNP) and 3,5‐dinitro‐3,5‐diazaheptane (DNG) from co‐crystals with CL‐20, leads to a noticeable decrease in the thermal stability of the latter . It has been suggested that due to the evaporation of volatile components, CL‐20 remained in amorphous form, which led to the disappearance of the stabilizing effect of the crystal lattice.…”
Section: Resultsmentioning
confidence: 99%